Improvement of Mustard-Boro-T. Aman Rice Cropping Pattern Through Replacing Crop Varieties For Tangail Region (Bangladesh Journal of Agricultural Research, 2023)
The experiment was conducted at the farmers field of FSRD site Atia, Delduar, Tangail during two consecutive years of 2018-19 and 2019-20 to develop improved cropping pattern Mustard (var. BARI Sarisha-14) - Boro (var. BRRI dhan29) - T.Aman rice (var. BRRI dhan72) and to compare its productivity and profitability against existing cropping pattern Mustard (var. Tori-7)- Boro (var. BRRI dhan29) - T.Aman rice (var. BR 11) through changing varieties of mustard and T.Aman rice with improved management practices. The experiment was laid out in a randomized complete block design with six dispersed replications. The improved management practice produced significantly higher yield in Mustard and T. Aman rice, respectively. The result showed that mean rice equivalent yield of improved cropping pattern was 16.80 t ha-1 which was 24 % higher than existing cropping pattern (13.50 t ha-1). Besides, production efficiency, land use efficiency, harvest index and profitability of improved cropping pattern was higher than farmers’ existing pattern. The mean gross return (Tk. 279720 ha-1) and gross margin (Tk. 104073 ha-1) were higher in improved cropping pattern compared to existing farmer’s pattern with only 7.82% extra cost. The marginal benefit cost ratio (4.05) also indicated the superiority of the improved cropping pattern over the farmers’ existing pattern.Bangladesh J. Agril. Res. 46(4): 397-406, December 2021